Le fratture della caviglia e del piede in età evolutiva - Samaila, E.M.; Paroni, C.; Vacchiano, A.; Magnan, B. (Lo Scalpello - Journal, 2018)
FOOT AND ANKLE FRACTURES Foot and ankle fractures represent 12% of all paediatric fractures. Physeal growth makes the paediatric patient’s bone different compared to that adults in term of diagnosis, treatment and complications. The diagnosis is based on clinical examination and conventional X-ray; CT scans are the gold standard for complex lesions. The most frequent complication of physeals injuries is the early closure of the growth plate with possible angular deformities and leg length discrepancy. Most injuries may be treated conservatively. Surgical treatment is necessary when anatomical reduction cannot be achieved.